The Potency of Chamomile Flowers (Matericaria chamomilla L.) as Feed Supplements (Growth Promoters) on Productive Performance and Hematological Parameters Constituents of Broiler - Al-Kaisse, Galib A.M.; Khalel, Eman K. (International Journal of Poultry Science, 2011)
The present study was carried out at the poultry farm, College of Veterinary Medicine-Baghdad University, to investigate the effect of adding dried milled of chamomile flowers to broiler diets on growth performance and some hematological traits. Two hundred fifty Rose broilers(day old chicks) were used in this study. Chicks were weighted and randomly distributed into (5) treatments, with (2) replicates (25 chicks of each). Chicks were fed the following diets. First group fed a basal diet without of any addition kept as a control group, while the (second 2nd, 3rd, 4th and 5th) groups were fed the same diet as in the 1st group plus addition of 0.25, 0.50, 0.75 and 1% of chamomile flowers powder. The experiment was lasted for (6) weeks age. Weight Gain (WG), Feed Intake (FI) and Feed Conversion Ratio (FCR) were measured. At the end of experiment samples were taken for blood parameter and carcasses traits. Results showed that for measurements adding of Chamomile flowers at a level of 0.75 and 1% increased significantly (p<0.05) Live Body Weight (LBW), (WG) and (FCR) as compared with the remaining groups, adding of chamomile flowers powder as a feed supplement with (0.75, 1%) levels were significantly (p<0.05) decreased (F1) as compared with control group. On the other hands all treatments revealed no significant differences on dressing percentage and giblets weight except liver weight. Adding of chamomile flowers with the above levels significantly (p<0.05) decrease in the (RBC, Hb, PCV) count compared with the control group but rather decreased cholesterol and glucose concentration in the blood serum especially at (0.50, 1%) as compared with the remaining groups, also adding chamomile flowers to diet showed significant decrease in H/L ratio, but showed no differences in (WBC) count.